2011
DOI: 10.1007/s00216-011-5600-4
|View full text |Cite|
|
Sign up to set email alerts
|

HS-SPME-GC×GC-qMS volatile metabolite profiling of Chrysolina herbacea frass and Mentha spp. leaves

Abstract: The definitive version is available at: La versione definitiva è disponibile alla URL: [http://link.springer.com/article/10.1007/s00216-011-5600-4#page AbstractHeadspace solid-phase microextraction (HS-SPME) comprehensive two-dimensional (2D) gas chromatography combined with quadrupole-mass spectrometry (GCxGC-qMS) with dedicated comparative data elaboration was applied to separate chemical patterns arising from the interaction between some Mentha species and the herbivore Chrysolina herbacea, also known as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…litura larvae are able to detoxify terpenes, including γ-terpinene [53][54][55]. The absence of chemical derivatives of O. vulgare terpenes and the assimilation of more than 50% of ingested terpenes by S. littoralis, as evidenced by our insect's frass analyses, show that S. littoralis catabolizes the plant terpenes and shows a limited ability to biotransform these molecules, in contrast to the typical behavior of specialist herbivores [56]. However, the catabolism of O. vulgare terpenes can produce also non-volatile derivatives which might not have been detected by our GC-MS and GC-FID analyses.…”
Section: Discussionmentioning
confidence: 99%
“…litura larvae are able to detoxify terpenes, including γ-terpinene [53][54][55]. The absence of chemical derivatives of O. vulgare terpenes and the assimilation of more than 50% of ingested terpenes by S. littoralis, as evidenced by our insect's frass analyses, show that S. littoralis catabolizes the plant terpenes and shows a limited ability to biotransform these molecules, in contrast to the typical behavior of specialist herbivores [56]. However, the catabolism of O. vulgare terpenes can produce also non-volatile derivatives which might not have been detected by our GC-MS and GC-FID analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Piperitenoneoxide is the main integral that is attributed to the insecticidal activity of the plant (LC50, 9.95 mg/L). [35] It is similarly shown that M. longifolia essential oil has 100% repellence against Sitophilus zeamais (10, 15, 20 days old),[3637] and Tribolium castaneum (25 days old). [38] Two studies have reported the high efficacy of the ethanolic extract of M. longifolia against third- and fourth-instar larvae of house mosquito Culex pipiens (LC50-26.8 ppm),[39] and against Sitophilus oryzae (24.2% repellency).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The utility of GC×GC for targeted analyses of biological samples as well as compound discovery in complex matrices, including untargeted metabolomics [3, 4], is well recognized and applicable to many areas of inquiry. For example, Hartman, et al report using GC×GC in targeted analyses to quantify 3,4-methylenedioxymethamphetamine and three of its metabolites in blood and serum [5], and in an untargeted metabolomics analysis, Cordero and colleagues applied GC×GC to the detection of previously unidentified volatile metabolites from the leaves of Mentha species [6]. Turning the large data sets that are generated by MDC methods into information (e.g., quantifiable peaks and compound identities) is becoming less time-intensive and more reliable through advancements in commercial software packages (e.g., ChromaTOF, GCImage, and ChromSquare), as well as new unsupervised data processing and statistical analysis methods that are being developed or retooled for MDC (recently reviewed in [712]).…”
Section: Introductionmentioning
confidence: 99%